Can the dialogic story reading approach enhance language, communication and relationships' in children with autism? - Lundy, Kathryn (My University, 2019)
Autism (ASD) is a developmental disorder which is characterised by challenges in social, emotional, language and communication skills. According to Irish legislation pertaining to the education for persons with special needs (2004), children with ASD have a right to receive an education that enables them to reach their full potential. Additionally the legislation states that children with ASD should be taught alongside their peers in mainstream classes where possible. The increase in numbers of children with ASD in mainstream classes has an impact on educators and students alike. Teachers are required to modify their educational practice to suit the individual needs of students with ASD. The dialogic story reading approach is cited as an effective literacy intervention for children who are typically developing and children with ASD. Furthermore, research has shown that this reading can be an effective tool to develop and enhance relationships between teacher and student. A living theory approach of action research is used to explore this issue with a view to improving and reflecting on current practice. The research took place with two children with ASD that are from the researcher's class. Data was obtained from recording the sessions and analysing the reflection diaries and revision cast recordings. This research found that the dialogic story reading approach was an effective intervention to promote language and communication with children with ASD. However, the strategy was more effective in a one to one setting. This is because the severity of ASD has an impact on a child's educational engagement and attainment.
Master in Education Studies (Early Childhood Education).
Keywords: Research Subject Categories; Autism (ASD); Developmental disorder; Effective literacy intervention; Mainstream classes